2006
DOI: 10.1021/la060280h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Oscillating Magnetic Field on the Release Properties of Magnetic Collagen Gels

Abstract: The paper describes the effect of an oscillating magnetic field (OMF) on the morphology and release properties of collagen gels containing magnetic nanoparticles and microparticles and fluorescent drug analogues. Collagen gels were prepared through fibrillogenesis of collagen in the presence of iron oxide magnetic particles averaging 10 nm or 3 mum in diameter and rhodamine-labeled dextran (Dex-R) of molecular weights between 3000-70 000 g/mol. Dextran molecules effectively simulate protein-based drugs, since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 36 publications
0
40
1
1
Order By: Relevance
“…In the presence of magnetic field, the magnetic core constituting the polymer-encapsulated nanoparticle carrier experiences mechanical deformation within the matrix, generating alternating compressive and tensile stresses. This provides a pumping Table 2 Assignment of FTIR spectra of as-synthesized magnetite nanoparticles, PEG-coated magnetite nanoparticles, pure folic acid and folic acid-modified, PEG-coated magnetite nanoparticles mechanism that enables diffusion of the drug out of the polymer shell [46][47][48]. If the PEG shell encapsulating the magnetic core was relatively thick, then the magnitude of modulation and consequent mechanical deformation experienced by the drug-conjugated PEG shell will be significantly reduced.…”
Section: Drug Release Responsementioning
confidence: 99%
“…In the presence of magnetic field, the magnetic core constituting the polymer-encapsulated nanoparticle carrier experiences mechanical deformation within the matrix, generating alternating compressive and tensile stresses. This provides a pumping Table 2 Assignment of FTIR spectra of as-synthesized magnetite nanoparticles, PEG-coated magnetite nanoparticles, pure folic acid and folic acid-modified, PEG-coated magnetite nanoparticles mechanism that enables diffusion of the drug out of the polymer shell [46][47][48]. If the PEG shell encapsulating the magnetic core was relatively thick, then the magnitude of modulation and consequent mechanical deformation experienced by the drug-conjugated PEG shell will be significantly reduced.…”
Section: Drug Release Responsementioning
confidence: 99%
“…who demonstrated insulin release from a magnetic composite of ethylene vinyl acetate under a low frequency magnetic field. [1][2] Recently, De Paoli et al [3] reported magnetically enhanced dextran release (which simulates protein release) from a magnetic nanocomposite made of a collagen gel. Magnetic biocompatible iron oxide nanoparticles were used in the latter study as in our previous work on ferrogels, [4] but they both involved bulk gels instead of colloids.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic hydrogels have also been produced by filling hydrogels with magnetic particles (e.g. maghemite, magnetite, cobalt-ferrite) [1], this procedure makes them more suitable for certain biomedical applications, such as drug delivery [1,6,7], enzyme immobilization [1,[8][9][10] or cancer therapy by the combination of controlled drug release and magnetic hyperthermia [1,11]. Magnetic hydrogels have been prepared by three, fundamentally different methods: blending, in situ precipitation and grafting-onto methods [1].…”
Section: Introductionmentioning
confidence: 99%